2019
DOI: 10.37107/jhas.59
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Blood Pressure Control among Hypertensive Patients of Pokhara Valley

Abstract: Hypertension is a chronic medical condition which remains inadequately managed everywhere. Medication adherence (MA) is a critical parameter for achieving strict blood pressure (BP) control in patients undergoing antihypertensive therapy (AHT). Good MA is also a key factor determining the success of preventive measures for cardiovascular (CV) risk reduction. So, the objective of this research was to study the medication adherence and blood pressure control among hypertensive patients of Pokhara Valley. A rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Out of 107 full-text articles that we assessed, 95 had either ineligible outcomes such as pulmonary hypertension, were conducted among non-hypertensive or non-Nepali participants, or were reviews, case reports or conference abstracts. We did the forward and backward citation tracking for the remaining 12 studies and identified two additional records ( 46 , 47 ). One additional study eligible report was identified on the Nepalese Government website.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of 107 full-text articles that we assessed, 95 had either ineligible outcomes such as pulmonary hypertension, were conducted among non-hypertensive or non-Nepali participants, or were reviews, case reports or conference abstracts. We did the forward and backward citation tracking for the remaining 12 studies and identified two additional records ( 46 , 47 ). One additional study eligible report was identified on the Nepalese Government website.…”
Section: Resultsmentioning
confidence: 99%
“…No additional eligible studies were found in Nepalese journals and on websites of Nepali professional and regulatory organisations, and national and international agencies. Finally, we included 15 studies (32,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59) for qualitative synthesis (Figure 2). None of the studies were included in the quantitative synthesis of effect sizes because of the significant differences in their aims, methods, interventions/exposures, and outcome measures.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 In Nepal, controlled blood pressure among hypertensive patients varies by geographical region and ranges from 35% 11 to 49% 12 in the Central Development Region and only 15% in the Western Development Region of Nepal. 13 Studies in Nepal have shown that self-reported adherence to antihypertensive medication varies from 35.4% to 64.3%, 14–16 leading to many complications.…”
Section: Introductionmentioning
confidence: 99%